ADAR2 affects mRNA coding sequence edits with only modest effects on gene expression or splicing in vivo. Issue 1 (2nd January 2016) - Dillman, Allissa A.; Cookson, Mark R.; Galter, Dagmar
ABSTRACT: Adenosine deaminases bind double stranded RNA and convert adenosine to inosine. Editing creates multiple isoforms of neurotransmitter receptors, such as with Gria2 . Adar2 KO mice die of seizures shortly after birth, but if the Gria2 Q/R editing site is mutated to mimic the edited version then the animals are viable. We performed RNA-Seq on frontal cortices of Adar2 -/- Gria2 R/R mice and littermates. We found 56 editing sites with significantly diminished editing levels in Adar2 deficient animals with the majority in coding regions. Only two genes and 3 exons showed statistically significant differences in expression levels. This work illustrates that ADAR2 is important in site-specific changes of protein coding sequences but has relatively modest effects on gene expression and splicing in the adult mouse frontal cortex.